Estratégias de coping e níveis de estresse em pacientes portadores de psoríase Coping strategies and stress levels in patients with psoriasis - Juliana Dors Tigre da Silva; Marisa Campio Muller; Renan Rangel Bonamigo (Anais Brasileiros de Dermatologia, 2006)
FUNDAMENTOS: Pesquisas atuais estão direcionando seu foco aos aspectos psicossociais envolvidos nas dermatoses crônicas. Esses fatores podem contribuir para a exacerbação da psoríase entre 40 e 80% dos casos, causando grande impacto na qualidade de vida desses pacientes. OBJETIVOS: Verificar estratégias de coping e identificar níveis de estresse do portador de psoríase. MÉTODOS: Estudo transversal, com amostra de 115 pacientes, divididos em 61 com psoríase e 54 do grupo controle com dermatoses crônicas. Instrumentos: Inventário de Estratégias de coping e Inventário de Sintomas de Estresse para Adultos de Lipp. RESULTADOS: Destacam-se as estratégias de coping autocontrole (p=0,027) e fuga e esquiva (p=0,014) utilizadas mais pelo grupo com psoríase e níveis de estresse altos para os dois grupos (p=0,838). CONCLUSÃO: Pacientes com psoríase utilizam estratégias de coping específicas para o enfrentamento da doença de pele, quando comparados a outros pacientes com doenças crônicas de pele demonstrando relevante nível de estresse. A integração dos resultados possibilita o entendimento do estado específico que portadores de psoríase vivenciam e que denuncia a premência de intervenções mais abrangentes que envolvam também as dimensões psíquica e social. ABSTRACT BACKGROUND: Psychosocial aspects are the current focus of research on chronic dermatoses. These aspects may contribute to exacerbation of psoriasis in 40 to 80% of cases, thus having great impact on patients’ quality of life. OBJECTIVES: This study aims to assess coping strategies and to identify stress levels of patients with psoriasis. METHODS: This is a cross-sectional study of a sample of 115 patients, which included 61 patients with psoriasis and 54 patients with other chronic dermatoses as controls. Instruments: The Ways of Coping Questionnaire and the Lipp Stress Symptoms Inventory for Adults. RESULTS: The coping strategies of self-control (p=0.027) and escape-avoidance (p=0.014) were the most used by patients with psoriasis and both groups present high stress levels (p=0.838). CONCLUSION: Patients with psoriasis use specific coping strategies to deal with their skin disorder when compared to other patients with chronic skin disorders; they also present stress levels as high as the control group. The integration of results enables understanding the special state of mind experienced by psoriasis patients to deal with the condition, thus showing the urgent need to develop broader intervention strategies, which also involve the social and psychic dimensions.